Guest

If‌ ‌we have an expression as 2x‌‌=‌‌3y‌‌=‌‌12z ,‌ ‌show‌ ‌that‌ ‌1z‌‌=‌‌1y‌‌+‌‌2x .‌

If‌ ‌we have an expression as 2x‌‌=‌‌3y‌‌=‌‌12z
,‌ ‌show‌ ‌that‌ ‌1z‌‌=‌‌1y‌‌+‌‌2x
.‌

Grade:12th pass

1 Answers

Pawan Prajapati
askIITians Faculty 60796 Points
2 months ago
Our expert is working on this Class VII Maths answer. We will update the answer very soon.

Think You Can Provide A Better Answer ?

Provide a better Answer & Earn Cool Goodies See our forum point policy

ASK QUESTION

Get your questions answered by the expert for free